(untitled) (Experimental biology, 2019)
Currently relevant are studies of plants, which contain a large number of biological active substances of different composition, that are sources of biotechnological products. The main purpose of this research work in the conditions of model experience was to determine the level of accumulation of biologically active substances contained in the aquatic plant Eichhornia crassipes, distributed in the lakes of Almaty region. Eichhornia crassipes can be considered as a promising object of higher aquatic plants, for which the composition of biologically active substances has not yet been studied. The practical significance of the study is to determine the medical value of biologically active substances of plants in lakes and reservoirs.We have determined the quantitative and qualitative composition of biological active substances from vegetative aboveground (leaves and stems) and underground parts (roots) of Eichhornia crassipes plant. According to the results of qualitative indicators were identified the biological active substances prevailing in composition, such as phenolic acids, flavonoids and polysaccharides. According to the results of quantitative indicators, in the aboveground part of plants the content of tannins amounted to 6.73%, polysaccharides 5.91%, flavonoids 3.39%, phenolic acids 1.06%, coumarins 0.82%, the most common biological active materials are tannins 7.48%, polysaccharides 2.64%, anthraquinones 2.59%, proteins 0.73%, alkaloids 0.13%. The obtained results are used as laboratory work to perform laboratory work at for research experiments in the laboratory biotechnology specialties and to determine the content of biologically active substances of plants. Keywords: Eichhornia crassipes, biologically active substances, tannins, polysaccharides.